Changing frames of mobility: the Stockholm congestion tax - Richardson, Tim; Isaksson, Karolina; Gullberg, Anders (Proceedings from the Annual Transport Conference at Aalborg University, 2008)
The introduction of a congestion tax was a significant moment in the management of mobility in Stockholm. After several decades of lobbying and political conflict, the tax was introduced as a trial 2006, consented to by citizens through a referendum, and then adopted permanently in the summer 2007. Consensus on addressing the problems caused by the car in the city appeared to have been reached, and the final scheme was introduced to international acclaim. This paper critically examines this apparent consensus on confronting car based mobility by analysing how mobility was framed at key stages in policy making since the 1970s through to the trial in 2006 and subsequent implementation. The analysis centres on the place of the car in successive framings of mobility. Changing targets and objectives for urban traffic management are compared, and an attempt is made to trace winners and losers in relation to motility and environmental quality. Overall the paper attempts to show how congestion taxation was framed and reframed to produce dramatically different possible mobility interventions. This analysis is used to argue that the framing of future mobility changed fundamentally by the time the final scheme was adopted, and that a moment of ambivalence about the car, during the trial, was not used to confront car based mobility. Instead a persuasive story of successful implementation has allowed a new car oriented mobility regime to slip into place under the veil of a progressive policy intervention.